Ultra-smooth and space-filling mineral films generated via particle accretion processes - Harris, Joseph; Mey, Ingo P.; Böhm, Corinna; Trinh, Huyen; Leupold, Simon; Prinz, Carsten; Tripal, Philipp; Palmisano, Ralf; Wolf, Stephan (Nanoscale Horizons, 2019)
Nonclassical crystallization typically yields materials with pronounced roughness and porosity as it is driven by nanoparticle self-organization. Here, we demonstrate that bio-inspired nonclassical mineralization via magnesium-doped polymer-induced liquid precursors (PILP) can yield ultra-smooth and space-filling CaCO3 films featuring an unprecedented low roughness of 0.285 nm.
CRIS-Team WoS Importer:2019-11-01